Impacts of anomalies in Arctic sea ice outflow on sea ice in the Barents and Greenland Seas during the winter-to-summer seasons of 2020 - Zhang, Fanyi; Lei, Ruibo; Pang, Xiaoping; Zhai, Mengxi; Li, Na (2023)
Arctic sea ice outflow to the Atlantic Ocean is essential to Arctic sea ice mass loss and the hydrographical and ecological environments in the Barents and Greenland Seas (BGS). In the context of the extremely positive Arctic Oscillation (AO) in January–March 2020, the impacts and feedback mechanisms on a seasonal scale of anomalies in Arctic sea ice outflow on winter–spring sea ice and other marine environmental conditions in the subsequent months until early summer in the BGS were investigated. The results reveal that the total sea ice area flux (SIAF) through the Fram Strait, the Svalbard-Franz Josef Land, and the Franz Josef Land-Novaya Zemlya passageways in January–March and June 2020 were higher than the 1988–2020 climatology, mainly through the Fram Strait (77.6 %). The interannual variability of this total SIAF was dominated by changes in ice motion speed ( R = +0.86, P < 0.001). The relatively high ice speed along the Transpolar Drift in January–June 2020 was related to the positive phases of winter (JFM) AO and the winter-spring air pressure gradient across the western and eastern Arctic Ocean. The abnormally high Arctic sea ice outflow led to an increased sea ice area and thickness in the BGS, which has been observed since March 2020, especially in May–June. In this region, the April sea ice area was significantly negatively correlated with synchronous sea surface temperature (SST) as well as the lagging SST of 1–3 months. High sea ice area in spring (AMJ) 2020 also inhibited phytoplankton bloom, with an extremely low Chlorophyll-a concentration observed over the BGS in April. Therefore, this study suggests that winter–spring Arctic sea ice outflow can be considered as a predictor of changes in sea ice and other marine environmental conditions in the BGS in the subsequent months, at least until early summer. The results increase our understanding of the physical connection between the central Arctic Ocean and the peripheral seas.